The Effect of Perceived Value and Team Identification on the Repeat Purchase of Persib Official Jersey Mediated By Bobotoh's Attitude in the City of Bandung - Ahmad Nizar Sadili; Eka Septiarini (LP2M IAIN Palopo, 2026)
The ever-increasing growth of the football club merchandise market shows that official merchandise has become an important part of the sports industry. However, even though Persib Bandung has a large and loyal supporter base, sales of Persib Official Jersey in the 2024/2025 season have decreased by around 20% due to the rampant circulation of pirated jerseys. This condition shows that there is a gap between Bobotoh's emotional attachment to the club and the behavior of buying official products. This study aims to analyze the influence of Perceived Value and Team Identification on Repeat Purchase by placing Attitude Bobotoh as a mediating variable. Quantitative methods were applied as an approach in this study. This study involved 138 respondents as a research sample. Respondents were selected based on the purposive sampling method included in the non-probability sampling technique. At the same time, data were obtained through the use of questionnaires that met the criteria of validity and realism and passed the classical assumption test. Furthermore, hypothesis testing was analyzed through multiple regression and sobel test using SPSS version 22. The results show that Perceived Value and Team Identification have a positive and significant influence on Bobotoh's Attitude. Perceived Value and Team Identification positively and significantly influence Repeat Purchase. In addition, Bobotoh's Attitude can mediate the influence of Perceived Value and Team Identification on Repeat Purchases.